‘Mental models’ that students possess about Work Integrated Learning (WIL) with reference to the New Curriculum Framework - Njozela, D (South African Journal of Higher Education, 2016)
Certain principles, processes and procedures inform the design and delivery of student’s lessons in teacher education. In mentoring students, it was discovered that they exhibit ‘mental models’ during evaluation and monitoring of their lessons that are different from what they were taught. This has a negative impact on the effectiveness of the lessons they conduct. Furthermore, the discovery exhibits tension between ‘museum possession of knowledge” as opposed to “workshop possession of knowledge’’ (Lubisi, Wedekind & Parker, 1998, 100). The paper explores the mental models that students possess in the design and delivery of their lessons against what policy requires them to do. The phenomenon is an indication of the ‘misfit’ between what the policy says and what is happening practically. It is believed that Work Integrated Learning is an important resource for students learning. Whilst this fact may be true, it needs constant monitoring, coaching reflection for it to achieve the desired outcome. For instance, students do not consider the importance of communicating outcomes to their learners. They think it is not important to unpack and discuss the journey that they embark on with their learners. This is an indication that the role of mediator of teaching and learning is strongly sacrificed yet learners take the blame for failure and lack of understanding. Key words: Knowledge management, designing a learning programme, reflective practice, learning strategies, fit between theory and practice, meaningful learning.